ELemental Abundances of Planets and Brown Dwarfs Imaged around Stars (ELPIS). II. The Jupiter-like Inhomogeneous Atmosphere of the First Directly Imaged Planetary-mass Companion 2MASS 1207 b - Zhoujian Zhang; Paul Mollière; Jonathan J. Fortney; Mark S. Marley (The Astronomical Journal, 2025)
2MASS 1207 b, the first directly imaged planetary-mass companion, has been instrumental in advancing our understanding of exoplanets and brown dwarfs over the past 20 yr. We have performed extensive atmospheric retrieval analyses of 2MASS 1207 b’s JWST/NIRSpec spectrum using petitRADTRANS and a new atmospheric inhomogeneity framework, which characterizes homogeneous atmospheres, patchy clouds, cloud-free hot spots, or the combination of patchy clouds and spots. Among 24 retrieval runs with various assumptions, the most statistically preferred model corresponds to the patchy cloud scheme, with ${T}_{{\rm{eff}}}=117{4}_{-3}^{+4}$ K, $log(g)=3.6{2}_{-0.02}^{+0.03}$ dex, and $R=1.39{9}_{-0.010}^{+0.008}$ R _Jup , along with near-solar atmospheric compositions of [M/H] = −0.05 ± 0.03 dex and C/O = 0.440 ± 0.012. This model suggests ∼9% of 2MASS 1207 b’s atmosphere is covered by thin iron and silicate clouds, producing L-dwarf-like spectra, while the remaining 91% consists of thick iron and silicate clouds, emitting blackbody-like spectra. These thin-cloud patches and thick-cloud regions resemble Jupiter’s belts and zones, respectively, and this scenario is consistently supported by other retrieval runs incorporating inhomogeneous atmospheres. We demonstrate that the weak CO absorption of 2MASS 1207 b can be explained by the veiling effects of patchy thick clouds; the absence of 3.3 μ m CH _4 absorption is attributed to its hot thermal structure, which naturally leads to a CO-dominant, CH _4 -deficient atmosphere. The retrieved atmospheric models also match the observed variability amplitudes of 2MASS 1207 b. Our analysis reveals that the inferred atmospheric properties show significant scatter in less statistically preferred retrieval runs but converge to consistent values among the preferred ones. This underscores the importance of exploring diverse assumptions in retrievals to avoid biased interpretations of atmospheric properties and formation pathways.